Rhythmic Cold Effect on Activity of Elastases in Female Rats with Alcohol-Dependent Hypertension - Samokhina, L. M.; Starodub, N. F.; Babiychuk, G. A.; Lomako, V. V. (Problems of Cryobiology and Cryomedicine, 2024)
Under the influence of rhythmic cold exposures (RCEs) in female rats with alcohol-dependent hypertension there was found a suppressed activity of elastases of different origin in tissues of brain cortex, lungs, heart, liver and kidneys lower than the control level. RCEs lead to oppositely directed changes in elastase-inhibitory activity (EIA) of alpha-1- proteinase inhibitor ( alpha-1-PI) caused by alcohol effect and namely to the rise in all the studied tissues except kidneys wherein there was found a decrease. Herewith if compared to the control EIA alpha-1-PI increased only in lungs and liver, i. e. in the sites of possible synthesis of this inhibitor. The absence of stimulating an inhibitory potential in brain cortex and heart is in accordance with local decrease of EIA alpha-1-PI in the control and may be stipulated with the fact that inhibitor does not enter from the synthesis sites.